2022
DOI: 10.3390/info13090411
|View full text |Cite
|
Sign up to set email alerts
|

Semantic Connections in the Complex Sentences for Post-Editing Machine Translation in the Kazakh Language

Abstract: The problems of machine translation are constantly arising. While the most advanced translation platforms, such as Google and Yandex, allow for high-quality translations of languages with simple grammatical structures, more morphologically rich languages still suffer from the translation of complex sentences, and translation services leave many structural errors. This study focused on designing the rules for the grammatical structures of complex sentences in the Kazakh language, which has a difficult grammar w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The BLEU score with the BPE segmentation reached the values of 0.23 and 0.22. In Turganbayeva et al (2022) , the grammatical structure of complex Kazakh sentences was observed. This study proved the methods used worked; however, they completely relied on the rule-based approach.…”
Section: Introductionmentioning
confidence: 99%
“…The BLEU score with the BPE segmentation reached the values of 0.23 and 0.22. In Turganbayeva et al (2022) , the grammatical structure of complex Kazakh sentences was observed. This study proved the methods used worked; however, they completely relied on the rule-based approach.…”
Section: Introductionmentioning
confidence: 99%
“…This complexity poses challenges for machine translation, as it is necessary to correctly interpret and translate each morpheme. Translation between Kazakh and languages with different morpho-logical structures, such as English, can lead to a lack or excess of information in the target text [25].…”
mentioning
confidence: 99%
“…In the software implementation, post-editing is carried out using both light and full post-editing modules and a rule-based approach. This approach allows for working with both simple and complex sentences [25].…”
mentioning
confidence: 99%